Chinese hamster ovary‐sphingomyelin synthase2 biospecific extraction and liquid chromatography with tandem mass spectrometry analysis for the prediction of bioactive components of Rhizoma Polygoni Cuspidati. Issue 6 (March 2016) - Xue, Ying; Dong, Jibin; Liang, Jianying
Abstract : A novel strategy for predicting bioactive components in traditional Chinese medicines using Chinese hamster ovary‐sphingomyelin synthase2 (CHO‐SMS2 ) cell biospecific extraction and high‐performance liquid chromatography with diode array detection and tandem mass spectrometry analysis was proposed. The hypothesis is that when cells are incubated with the extract of traditional Chinese medicines, the potential bioactive components in the traditional Chinese medicines should selectively combine with the cells, while the cell‐combining components would be detectable in the extract of denatured cells. The identities of the cell‐combining components could be determined by liquid chromatography with tandem mass spectrometry. Using the proposed approach, the potential bioactive components of Rhizoma Polygoni Cuspidati, a commonly used traditional Chinese medicine for atherosclerosis, were detected and identified. Eight compounds in the extract of Rhizoma Polygoni Cuspidati were detected as the components selectively combined with CHO‐SMS2 cells, which is a stable cell line that highly expresses sphingomyelin synthases, it was found that piceid, resveratrol, emodin‐8‐β‐d‐ glucoside, physcion‐8‐β‐d‐ glucoside, emodin, physcion, 3, 5, 4'‐trihydroxystilbene‐3‐ O ‐(6"‐galloyl)‐glucoside, and emodin‐1‐ O ‐glucoside combined specifically with CHO‐SMS2 cells. The results indicate that the proposed approach may be applied to predict the bioactive candidates in traditional Chinese medicines.